Amphiregulin impairs apoptosis-stimulating protein 2 of p53 overexpression–induced apoptosis in hepatoma cells. Issue 3 (March 2017) - Liu, Kai; Lin, Dongdong; Ouyang, Yabo; Pang, Lijun; Guo, Xianghua; Wang, Shanshan; Zang, Yunjin; Chen, Dexi
Overexpression of apoptosis-stimulating protein 2 of p53 (ASPP2) induces apoptotic cell death in hepatoma cells (e.g. HepG2 cells) by enhancing the transactivation activity of p53, but long-term ASPP2 overexpression fails to induce more apoptosis since activation of the epidermal growth factor/epidermal growth factor receptor/SOS1 pathway impairs the pro-apoptotic role of ASPP2. In this study, in recombinant adenovirus-ASPP2-infected HepG2 cells, ASPP2 overexpression induces amphiregulin expression in a p53-dependent manner. Although amphiregulin initially contributes to ASPP2-induced apoptosis, it eventually impairs the pro-apoptotic function of ASPP2 by activating the epidermal growth factor/epidermal growth factor receptor/SOS1 pathway, leading to apoptosis resistance. Moreover, blocking soluble amphiregulin with a neutralizing antibody also significantly increased apoptotic cell death of HepG2 cells due to treatment with methyl methanesulfonate, cisplatin, or a recombinant p53 adenovirus, suggesting that the function of amphiregulin involved in inhibiting apoptosis may be a common mechanism by which hepatoma cells escape from stimulus-induced apoptosis. Thus, our data elucidate an apoptosis-evasion mechanism in hepatocellular carcinoma and have potential implications for hepatocellular carcinoma therapy.